Pendampingan segmentasi Pasar dan Buyer Persona pada Pelaku UMKM di Kabupaten Tulungagung - Sendy Marcello Edy Putra; Serli Puspa Andini; Fitriani Eka Hariyati; Binti Nur Asiyah (Indo Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting local economic growth, yet most MSME actors in Tulungagung Regency still rely on mass marketing approaches without clear market segmentation and have limited understanding of the buyer persona concept, resulting in promotions that are untargeted and inefficient. This community service activity aimed to enhance MSME actors’ understanding of the importance of market segmentation, assist them in determining appropriate target markets, and guide them in developing buyer personas as the basis for more effective marketing strategies. The activity employed a service learning approach implemented through five stages, namely observation, socialization, mentoring, implementation, and evaluation, conducted directly over approximately five days with nine MSME partners in the culinary and beverage sector in Tulungagung Regency. The results showed that all nine MSME partners successfully identified their market segments based on demographic, geographic, psychographic, and behavioral aspects, and each developed a specific buyer persona reflecting their ideal customer’s characteristics, needs, and digital habits. The mentoring also produced tailored marketing strategy recommendations for each business, including social media content optimization, product variation, and service improvement aligned with target segments. These outcomes indicate that the practice-based mentoring approach effectively improved MSME actors’ comprehension and practical skills in designing consumer data-driven marketing strategies, thereby strengthening their business competitiveness. Continued mentoring is recommended to enable MSMEs to adapt their marketing strategies to evolving consumer behavior and market dynamics.